2015
DOI: 10.1108/oclc-06-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

Scalable decision support for digital preservation: an assessment

Abstract: Structured Abstract:Purpose -Scalable decision support and business intelligence capabilities are required to effectively secure content over time. This article evaluates a new architecture for scalable decision making and control in preservation environments for its ability to address five key goals: (1) Scalable content profiling, (2) Monitoring of compliance, risks and opportunities, (3) Efficient creation of trustworthy plans, (4) Context awareness, and (5) Loosely-coupled preservation ecosystems.Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…C3PO uses MongoDB as storage and queries the data using map-reduce jobs. While this can in principle provide highly scalable analytics, previous research on a very large test data set highlighted that the platform was not sufficiently scalable for large data sets [7,29].…”
Section: Scalabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…C3PO uses MongoDB as storage and queries the data using map-reduce jobs. While this can in principle provide highly scalable analytics, previous research on a very large test data set highlighted that the platform was not sufficiently scalable for large data sets [7,29].…”
Section: Scalabilitymentioning
confidence: 99%
“…For example, the File Information Toolset (FITS) 1 fuses multiple tool outputs and marks any contradictions between the tools in the combined output it produces. The content profiling platform C3PO exposes these conflicts so that they cannot be missed, but does not resolve them [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Becker et al (2015), we will conduct a systematic assessment of the system based on the design goals outlined in this article. We will discuss the improvements of the presented work and identified limitations, based on a quantitative and qualitative evaluation including a case study with a national library.…”
Section: Discussionmentioning
confidence: 99%
“…Section 4 presents the suite of automated tools designed and developed to improve decision support and control in real-world settings. Becker et al (2015) will discuss the improvements of the presented work and identified limitations, based on a quantitative and qualitative evaluation of advancing the state of art including a case study with a national library.…”
Section: Introductionmentioning
confidence: 99%
“…This is increasingly feasible (Holden, 2012) and has been done for a substantial set of the UK Web Archive (Jackson, 2012). For example, a dataset from the Danish web covers 8 years in 441 million files (Becker, Faria, & Duretec, 2015). It contains in-depth, detail-rich feature sets extracted by the File Information Toolset (FITS), but covers fewer years.…”
Section: Significant Time Spanmentioning
confidence: 99%